(untitled) (Research, Society and Development, 2025)
Environmental information has been increasingly used to better guide sustainable agriculture. The use of the Environmental Information Bank (BDiA) informs the types of soils occurring in the municipality of Alta Floresta-MT and their physical, chemical and morphological characteristics. This study aimed to analyze the use of BDiA digital tools, specifically in the interpretation of pedological maps in the municipality of Alta Floresta, in the state of Mato Grosso. BDiA is a database that gathers information on different environmental aspects, including soil characteristics, vegetation, geomorphology, and geology. The BDiA application provided by the Brazilian Institute of Geography and Statistics (IBGE) was used as methodological procedures. For this research, pedological data were used, which were later edited to better represent the analysis and soil mapping in the municipality. Fourteen sampling collection points were taken from BDiA, and the soil was interpreted and analyzed through secondary data. The soils present great diversity in the municipality of Alta Floresta, nine profiles of ARGISSOLO VERMELHO-AMARELO (PVA), two profiles of NEOSSOLO QUARTZARÊNICO (RQ), two profiles of LATOSSOLO VERMELHO-AMARELO (LVA), and one profile of CAMBISSOLO HÁPLICO (CX) were described. It was concluded that the use of BDiA in the production and interpretation of pedological maps has significant implications for the environmental area and, from the moment in which more accurate and updated information about the soils is available, it is possible to develop more effective management and conservation strategies.